La gestión administrativa y financiera y su incidencia en la rentabilidad de la Cooperativa de Ahorro y Crédito Educadores de Chimborazo de la ciudad de Riobamba, periodo 2014. Manual financiero - Sánchez Zurita, Alexander Shasmany (2016)
ADMINISTRATIVE AND FINANCIAL MANAGEMENT AND ITS IMPACT ON THE RETURN ON COOPERATIVA DE AHORRO Y CRÉDITO EDUCADORES DE CHIMBORAZO DE LA CIUDAD DE RIOBAMBA, 2014. FINANCIAL PERIOD MANUAL. For the investigation he/she thought about the following general objective: To analyze the incidence of the administrative and financial administration in the profitability of the Savings and loan cooperative “Educators of Chimborazo” Ltda., of which you ends up settling down that the appropriate application of norms and political of supervision, control and financial and administrative wisdom, they contribute to that the profitability of the institution improves in a sustained and sustainable way. The proposed investigation was carried out through the explanatory, causal and hypothetical paradigms that he/she allows to explain by means of the logical, reasoned and conceptual argument of the facts and data related with the investigation topic, as well as the goods that it originates the absence of internal check norms in the Cooperative. When concluding the investigation you reached the following conclusion: The absence of an internal check system impacts in the results of the administrative and financial administration, for what is important to put into practice the proposed System, with the purpose of achieving the objectives and institutional goals in the short term.